Relasi Sosial Produksi dan Konflik Kepentingan Ekonomi dalam Perkebunan Kelapa Sawit Petani Swadaya: Studi Kasus Kabupaten Sintang, Kalimantan Barat - Borni Kurniawan, Kharis Fadlan; Dharmawan, Arya Hadi; Sumarti, Titik; Maksum, Mohammad (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
An agricultural partnership is one of the ways adopted by oil palm plantation smallholders to survive and be sustainable in the face of global competition. The agricultural partnership that is based on a contract agreement is also aimed at maintaining the welfare of the involved smallholders. Partnership in agricultural production is part of the management system or mode of economic production agreed upon by both large-scale companies and smallholders. An unbalanced arrangement sometimes occurs due to the power dominance of large-scale company interests that leads to unfair relationships in the partnership between smallholders and large-scale corporations. This study used a qualitative research method with a case study as the main approach. By taking the case of the agricultural partnership of oil palm plantation smallholders in Perembang Village and Begori Village, Regency of Sintang of West Kalimantan, this study found four typologies of social agricultural production relations, namely asymmetric partnership, exploitative partnership, distrust partnership, and forced partnership.